Chemical Concepts Related to the Context of Palm Oil Production Process for Contextual Chemistry Learning based on Local Natural Resources - Shalsabila, Syifa Yulia; Kusumaningtyas, Pintaka; Erika, Farah (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Chemistry learning oriented to local natural resources around students presents real situations that can help students to understand the concepts of learning material being studied. This research aims to identify the chemical concepts involved in the process of palm oil production for developing contextual chemistry learning materials based on local natural resources. This research used descriptive quantitative research. Data were collected from field observation, literature study and documentation study. The relevance of chemical concepts and the context of palm oil processing were assessed by the validators. Based on the finding, there are 3 chemical concepts related to the palm fruit processing into crude palm oil (CPO), namely: classification of matter,change of matter, and separation of mixture. The relationship between both of these three chemical concepts and the context of palm oil processing has been declared highly valid with a score of 3.75 by the validators. Therefore, the processing of palm fruit into CPO can be used as a learning resource for contextual chemistry learning material in the implementation of Merdeka curriculum at phase E.